Horizontal-cell like Dm9 neurons in Drosophila modulate photoreceptor output to supply multiple functions in early visual processing - Schnaitmann, Christopher; Pagni, Manuel; Meyer, Patrik B.; Steinhoff, Lisa; Oberhauser, Vitus; Reiff, Dierk F. (Frontiers in Molecular Neuroscience, 2024)
Dm9 neurons in Drosophila have been proposed as functional homologs of horizontal cells in the outer retina of vertebrates. Here we combine genetic dissection of neuronal circuit function, two-photon calcium imaging in Dm9 and inner photoreceptors, and immunohistochemical analysis to reveal novel insights into the functional role of Dm9 in early visual processing. Our experiments show that Dm9 receive input from all four types of inner photoreceptor R7p, R7y, R8p, and R8y. Histamine released from all types R7/R8 directly inhibits Dm9 via the histamine receptor Ort, and outweighs simultaneous histamine-independent excitation of Dm9 by UV-sensitive R7. Dm9 in turn provides inhibitory feedback to all R7/R8, which is sufficient for color-opponent processing in R7 but not R8. Color opponent processing in R8 requires additional synaptic inhibition by R7 of the same ommatidium via axo-axonal synapses and the second Drosophila histamine receptor HisCl1. Notably, optogenetic inhibition of Dm9 prohibits color opponent processing in all types of R7/R8 and decreases intracellular calcium in photoreceptor terminals. The latter likely results from reduced release of excitatory glutamate from Dm9 and shifts overall photoreceptor sensitivity toward higher light intensities. In summary, our results underscore a key role of Dm9 in color opponent processing in Drosophila and suggest a second role of Dm9 in regulating light adaptation in inner photoreceptors. These novel findings on Dm9 are indeed reminiscent of the versatile functions of horizontal cells in the vertebrate retina.